2013
DOI: 10.1002/anie.201300763
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Fluorinated Heteroarylether Bioisosteres

Abstract: This work delineates a method for the modular synthesis of reagents that are capable of direct incorporation of difluoroalkyl groups onto heterocycles. The scope and generality of this method is exemplified with the difluoroethyl group (along with the introduction of a new reagent for difluoroethylation, DFES-Na) and a proof of principle is shown for a general synthesis of fluorinated heteroarylether bioisosteres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
120
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(125 citation statements)
references
References 14 publications
3
120
0
2
Order By: Relevance
“…Comparison of these literature results with regiochemical perferences observed in our previous studies using radicals derived from alkylsulfinate salts 6 revealed some of the same trends as well as some contrasting observations (Equation 1). Substitution at the α and γ positions of pyridine is generally preferred, although some C3 substitution was observed on pyridines with CN, CO 2 Et or Ac groups at C4.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Comparison of these literature results with regiochemical perferences observed in our previous studies using radicals derived from alkylsulfinate salts 6 revealed some of the same trends as well as some contrasting observations (Equation 1). Substitution at the α and γ positions of pyridine is generally preferred, although some C3 substitution was observed on pyridines with CN, CO 2 Et or Ac groups at C4.…”
Section: Introductionsupporting
confidence: 80%
“…In our ongoing studies into the functionalization of heteroarenes using alkylsulfinate-derived radicals, 6 we have begun to observe certain trends pertaining to regiocontrol that – based upon the similarity to patterns observed in various other radical-mediated functionalization reactions – could be useful in a more general manner. In this full report, an extensive study of the reactivity trends of heteroarene functionalizations employing alkylsulfinate-derived radicals is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the regioselectivity is orthogonal to that observed for the Friedel-Crafts reaction, thus increasing the appeal of such transformations. Traditionally, carboxylic acids 5 and halides 6 have been employed as radical precursors, but more recently the toolbox has been expanded to include alcohols, 7 boronic acids, 8 sulfinate salts, 9 alkenes, 10 and alkyltrifluoroborates. 11 However, in most of the previous contributions, high temperatures, (sub)stoichiometric amounts of expensive metal salts, an excess of the radical precursor, and strong oxidants or expensive photocatalysts 7,11a,12 are required to achieve good yields.…”
Section: Introductionmentioning
confidence: 99%
“…The decoration of C–H bonds on heteroarenes using radicals generated from sulfinate salts has emerged as a predictable and chemoselective method for both the early and late stages of a synthesis, 1 for the prediction and prevention of drug metabolism, 2 and for the native chemical tagging of complex molecules. 3 In a recent report, a sulfinate salt was used to append a trifluoromethyl group onto (−)-agelastatin A, which led to the synthesis of the most potent derivative of this natural product.…”
mentioning
confidence: 99%
“…These findings are consistent with our previous studies where Minisci conditions generally fail when using fluorinated acids. 1 We then turned to Barton’s classic work on visible light mediated photolytic radical formation from O -esters of thiohydroxamic acids. 7 Acid 1 was converted to ester 3 , which was subjected to Barton’s conditions for the generation of alkyl radicals and Minisci-type addition in the presence of a Brønsted acid.…”
mentioning
confidence: 99%